Multiomics analysis reveals a distinct response mechanism in multiple primary lung adenocarcinoma after neoadjuvant immunotherapy. Issue 4 (5th April 2021) - Zhang, Chao; Yin, Kai; Liu, Si-Yang; Yan, Li-Xu; Su, Jian; Wu, Yi-Long; Zhang, Xu-Chao; Zhong, Wen-Zhao; Yang, Xue-Ning
Abstract : Multiple primary lung cancer (MPLC) remains a tough challenge to diagnose and treat. Although neoadjuvant immunotherapy has shown promising results in early stage non-small cell lung cancer, whether such modality can benefit all primary lesions remains unclear. Herein, we performed integrated multiomics analysis in one patient with early stage MPLC with remarkable tumor shrinkage in a solid nodule and no response in two subsolid nodules after treatment with three cycles of neoadjuvant pembrolizumab. Genomic heterogeneity was observed among responding nodules with high levels of infiltrating CD8 + and CD68 + immune cells. Substantially downregulated human leukocyte antigen (HLA)-related genes and impaired T lymphocyte function were observed in non-responding nodules. A larger proportion of infiltrating tissue resident memory T cells (Trm) along with high T cell receptor repertoire clonality in responding nodules were validated as predictive and prognostic biomarkers in multiple cancer types using external public datasets. These results suggested that neoadjuvant programmed death 1 (PD-1)/programmed death ligand 1 inhibitors alone may not be an optimal therapeutic strategy for MPLC due to disparities in genomic alterations and immune microenvironment among different lesions. Additionally, we postulate that increased infiltration of Trm may be a unique marker of early immune responses to PD-1 blockade.